Pengaruh Kualitas Pelayanan, Atmosfer dan Positive Emotion terhadap Revisit Intention pada Tahoma Cafe and Eatery - Ni Kadek Erika Asih Arsana Dewi; I Nengah Wirsa (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study examines the influence of service quality, cafe atmosphere, and positive emotions on revisit intention at Tahoma Café & Eatery in Denpasar, Bali. Using a quantitative approach and non-probability (accidental) sampling technique, 108 customers (Likert scale 1–5) completed a questionnaire that was valid (r > 0.30) and reliable (Cronbach's α > 0.70). Analysis using multiple linear regression in SPSS after all classical assumption tests were met (normality, no multicollinearity, and homoscedasticity). The results show that service quality (β = 0.380; p < 0.001), atmosphere (β = 0.304; p < 0.001), and positive emotions (β = 0.188; p < 0.001) have a positive and significant effect on revisit intention; Simultaneously, the model was significant (F = 72.339; p < 0.001) with clear capability (Adjusted R² = 0.667). Service quality is superior and responsive, combined with a comfortable atmosphere and positive emotions among visitors, which are the key to building loyalty and repeat visits in the cafe business.